The Effect of Implementing Artificial Intelligence-Based Interactive Learning Media on Enhancing Students’ Digital Literacy and Higher-Order Thinking Skills - Dewi Ratih; Abdul Haris Odja; Raghel Yunginger (Jurnal Pendidikan Fisika dan Teknologi (JPFT), 2026)
In recent years, Artificial Intelligence (AI) has created transformative opportunities for educational systems worldwide. AI is no longer viewed merely as a theoretical concept; rather, it has been integrated into various educational applications, including adaptive learning recommendation systems, virtual tutors, learning chatbots, and AI-powered interactive learning media. In 21st-century education, two essential competencies are digital literacy and Higher-Order Thinking Skills (HOTS). Digital literacy refers to the ability to access, evaluate, utilize, and manage information effectively and ethically within digital environments. Meanwhile, HOTS encompasses students’ abilities to analyze, synthesize, evaluate, solve problems, and create, representing cognitive skills that extend beyond basic memorization and comprehension. This study aims to examine the effect of implementing Artificial Intelligence (AI)-based interactive learning media on improving students’ digital literacy and Higher-Order Thinking Skills (HOTS). The study employed a qualitative descriptive approach through a literature review of 40 scientific articles, which were subsequently narrowed down to 13 relevant articles published between 2020 and 2025. The findings reveal that the implementation of AI-based learning media, such as educational chatbots, Gamma App, Canva AI, QuillBot, ChatGPT, PhET Simulation virtual laboratories, and intelligent tutoring systems, has a positive impact on enhancing students’ digital literacy and higher-order thinking skills. The integration of AI in learning encourages students to think critically, creatively, and adaptively in response to ongoing digital technological developments. Furthermore, the study highlights the importance of improving teachers’ competencies, strengthening digital infrastructure, and developing ethical and pedagogical guidelines for the effective use of AI in educational settings.